Political Participation of Millennials and Gen Z: Transformation of Youth Voter Engagement Patterns in Indonesia's Electoral Democracy System - Saragih, Mujahid Widian; Pirandy, Gusti; Damanik, Fritz Hotman Syahmahita (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
The transformation of Indonesia's political landscape is marked by the emergence of millennials (born 1981-1996) and Gen Z (born 1997-2012) as new political forces reshaping electoral participation dynamics. This study analyzes the political engagement patterns of young voters in Indonesia's democratic system using qualitative and quantitative approaches. Data were collected through surveys of 850 respondents aged 17-40 across five provinces, in-depth interviews with 45 key informants, and social media content analysis. Findings reveal that millennials and Gen Z exhibit distinct participation patterns from previous generations, characterized by digital platform utilization, issue-centric orientation, and skepticism toward traditional political institutions. Results show that 67.3% of young voters prioritize specific issues over party affiliation, 72.8% use social media as their primary source of political information, and 58.4% demonstrate preference for independent or non-partisan candidates. This study identifies three major transformation dimensions: digitalization of political activism, depersonalization of partisan loyalty, and democratization of political information access. The theoretical implications enrich discourse on political participation theory in digital society contexts, while practical implications provide guidance for political elites and democratic institutions in accommodating young voters' aspirations.